2016
DOI: 10.1097/aln.0000000000000969
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles for MicroRNAs in Perioperative Medicine

Abstract: MicroRNAs (miRNAs) are small, non–protein-coding, single-stranded RNAs. They function as posttranscriptional regulators of gene expression by interacting with target mRNAs. This process prevents translation of target mRNAs into a functional protein. miRNAs are considered to be functionally involved in virtually all physiologic processes, including differentiation and proliferation, metabolism, hemostasis, apoptosis, and inflammation. Many of these functions have important implications for anesthesiology and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 153 publications
(171 reference statements)
0
35
0
1
Order By: Relevance
“…miRNAs are involved in almost all aspects of biological processes involving development, cellular differentiation, immune modulation, and pathogenic conditions. miRNAs alter mRNA function via blockade of translation or RNA degradation and it is predicted that approximately 60% of human genes are controlled by miRNAs . The specificity of mRNA targeting relies on a sequence of the miRNA, termed the ‘seed’ sequence, that binds complementary to the 3′ untranslated region (3′UTR) of the mRNA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are involved in almost all aspects of biological processes involving development, cellular differentiation, immune modulation, and pathogenic conditions. miRNAs alter mRNA function via blockade of translation or RNA degradation and it is predicted that approximately 60% of human genes are controlled by miRNAs . The specificity of mRNA targeting relies on a sequence of the miRNA, termed the ‘seed’ sequence, that binds complementary to the 3′ untranslated region (3′UTR) of the mRNA .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs alter mRNA function via blockade of translation or RNA degradation and it is predicted that approximately 60% of human genes are controlled by miRNAs. [1][2][3][4][5][6][7] The specificity of mRNA targeting relies on a sequence of the miRNA, termed the 'seed' sequence, that binds complementary to the 3 ′ untranslated region (3 ′ UTR) of the mRNA. 8 Thus one miRNA is capable Abbreviations: 3 ′ UTR, 3 ′ untranslated region; ALI, acute lung injury; ARDS, acute respiratory distress syndrome; BALF, bronchial alveolar lavage fluid; BM, bone marrow; DAMP, damage-associated molecular patterns; DC, dendritic cell; DGCR8, DiGeorge syndrome chromosomal region 8; DSS, dextran sodium sulfate; IBD, inflammatory bowel disease;…”
Section: Introductionmentioning
confidence: 99%
“…However, this study has several limitations. The goal of miRNA overexpression is to restore physiological levels of miRNA for optimal function and avoid unwanted side effects of high levels of miRNA21. However, neither lentiviral-mediated overexpression of miR-365 nor a miR-365 mimic can satisfy these requirements.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been shown to modulate expression of various genes in different systems14151617. Recent studies have found miRNAs are also involved in perioperative medicine, including inflammation, ischemia, sepsis and mediating anesthetic toxicity1819202122. However, the specific role of miRNAs in morphine tolerance is still poorly understood.…”
mentioning
confidence: 99%
“…Downregulation of these miRNAs improved survival, learning, and behavioral performance in mice. Ketamine is also employed as an anesthetic, and the miRNA expression changes after exposure to fixed anesthetics, including propofol and ketamine, have been reviewed recently (Neudecker, Brodsky, Kreth, Ginde, & Eltzschig, 2016).…”
Section: Non-opioid Analgesicsmentioning
confidence: 99%